Sasaran Dakwah dalam Perspektif Diri Sendiri, Keluarga, Masyarakat dan Bangsa (Tafsir Tematik Komunikasi Islam - Andi Kardian Riva'i; Muhammad Fikri Vernanda (JURNAL SOSIO-KOMUNIKA, 2023)
The dynamics of society and advances in technology demand that da'wah activities not only use conventional-traditional methods, dealing directly with da'wah audiences, but shifting to the use of digital media as an instrument for the continuation of da'wah in the current era regardless of whether it applies to oneself, family or society. and nation. This paper is expected to broaden knowledge, especially on the theme of objects or targets of da'wah in the Koran: self, family, community and nation. The method used is library research, namely by collecting data related to the theme of discussion and problems taken from library sources. There are two main substance of da'wah targets: a). oneself, namely: knowledgeable and practicing it (Al-Baqarah, 44); practicing conformity between words and deeds is an obligation to achieve a degree of perfection (Ash-Shaff, 2 and 3); b). family, community and nation, namely: giving warnings and perfecting da'wah to others in order to get the good of Religion and the World (Asy-Syuara, 214); gentle demeanor and speech reflect the morals of the Prophet; Rude attitude broke the da'wah relationship (Asy-Syuara, 215); escape from iniquity (Asy-Syuara, 216); and not letting go, but trying to invite goodness (Tafsir Al-Munir, Wahbah Az-Zuhaili); Don't be apathetic if people reject the Qur'an; if there are humans who go so far as to commit violations, then there is nothing to be afraid of (Inspirational Tafsir, Zainal Arifin Zakaria)